A novel insight into ComE-mediated activation of gene expression in Streptococcus mutans - Hemendra Pal Singh Dhaked; Saswati Biswas; Indranil Biswas (Microbiology Spectrum)
ABSTRACT Bacteria use two-component signal transduction systems (TCSs) to sense and respond to environmental changes. TCSs comprise a histidine kinase that senses environmental signals and a response regulator that regulates cognate promoters. Most response regulators are incapable of regulating their promoters in the absence of the cognate histidine kinases. Here, we demonstrated that constitutive expression of the well-studied response regulator ComE of Streptococcus mutans (a dental pathogen) activates the nlmA promoter (PnlmA) for bacteriocin production without the involvement of its cognate histidine kinase ComD. To confirm the phosphorylation-independent role of ComE, we generated a phospho-mimicking (D60E) and a phospho-inactivating (D60A) variant and examined their ability to activate PnlmA in a ΔcomD knockout strain. We found that the phospho-mimicking D60E variant was able to induce the PnlmA expression. However, we also found that the phospho-inactivating variant also activates PnlmA. Furthermore, an in vitro binding assay suggested that both the phospho-mimicking and the phospho-inactivating variants were able to bind to PnlmA. Using a Phos-Tag gel analysis, we confirmed that the D60 of ComE is responsible for phosphorylation. Overall, this study demonstrated the autonomous role of the response regulator ComE by modulating the expression of its cognate promoters. We believe that other streptococcal ComE homologs might activate their target genes in a phosphorylation-independent manner similar to S. mutans ComE.IMPORTANCEBacteria utilize two-component signal transduction systems to detect and respond to environmental changes, typically involving a histidine kinase and a response regulator. While most response regulators need their cognate histidine kinases to modulate gene expression, our study shows that the response regulator ComE in Streptococcus mutans, a dental pathogen, can activate bacteriocin production without its cognate histidine kinase ComD. This study indicates that ComE can autonomously modulate promoter expression, suggesting similar mechanisms in other streptococcal ComE homologs.